Bidirectional leader development in sprite‐producing positive cloud‐to‐ground flashes: Origins and characteristics of positive and negative leaders. Issue 22 (21st November 2014) - van der Velde, Oscar A.; Montanyà, Joan; Soula, Serge; Pineda, Nicolau; Mlynarczyk, Janusz
Abstract Thirty‐five sprite‐producing lightning flashes were recorded in nine nights in different seasons at the east coast of Spain with a 3D Lightning Mapping Array (LMA) since July 2011. A low‐frequency time‐of‐arrival network provided data on emissions from return strokes and intracloud processes and a very‐high‐frequency interferometer network produced complementary lightning data. This study analyzes the bidirectional development of flashes in order to understand the positioning and timing of the positive cloud‐to‐ground stroke (+CG) and its consequences for charge neutralization by negative leaders, affecting sprite morphology. A summary of negative leader extents, altitudes, and speeds before and after the + CG stroke is provided, as well as positive leader origins and inferred speeds. Negative leader speeds exhibited modes at 105 and 5 × 105 m s−1. Five examples with different evolutions are discussed: (1) Slow bidirectional development with negative leader termination before the + CG stroke; (2) Fast bidirectional development with the negative leader continuing after the + CG stroke. (3) Slow‐fast bidirectional development with a negative leader exhibiting a sudden lowering and speed increase; (4) Fast secondary bidirectional development from an in‐cloud horizontal positive leader. Negative leaders propagated rapidly into the upper positive charge layer, continuing after the + CG stroke; (5) Slow bidirectional development with a long negative leader (50 km) subject to cutoff while the original positive leader remained trapped inside negative charge. A + CG stroke subsequently occurred under the old negative leader channel. Carrot sprites tended to be associated with fast extending leaders after the stroke, columniform/mixed sprites with slower side branches.